Walking activity increases physical abilities and subjective health in people with seven different types of disabilities - Selanon, Pattamon; Chuangchai, Warawoot (Frontiers in Public Health, 2023)
Introduction People with disabilities have a great risk of physical inactivity, which causes several diseases, dependency, and long-term care. Walking helps to increase physical activity, which leads to better overall health and independence. However, less research attention has focused on walking for people with disabilities, and even fewer studies have been considered for different types of disabilities. The present study aimed to demonstrate how walking distance was associated with people with seven different types of disabilities— including visual, hearing, physical/mobility, intellectual, learning, autism, and emotional/behavioral disabilities—in terms of their physical abilities and subjective health. Methods A total of 378 participants (aged 13–65) were gathered from seven national organizations in Thailand. A survey questionnaire on aspects of physical abilities (i.e., walking distance or manually rolling wheelchair distance; body balance; weightlifting; exercise duration and frequency); and subjective health (i.e., health status and satisfaction) was completed online by all participants. Results The walking distance was partially positive and associated with exercise duration, weightlifting, exercise frequency, and health status (all p values < 0.001), as well as body balance and health satisfaction (p = 0.001 and 0.004, respectively), after controlling for age, sex, and types of disability. This demonstrated that increasing the amount of distance walked could well lead to a more positive body and mind. Discussion The present study suggests that the possibility of having a walk and/or encouraging people with disabilities to walk for greater distances can have a significant impact on both their physical and subjective health outcomes.